Cyber Empathy dalam Era Komunikasi Virtual: Kajian Psikologis Tentang Empati di Dunia Digital - Dewi Tri Novitasari; Melani Cahyaningtyas; Putri Maharani; Konto Iskandar Dinata (CV. Doki Course and Training, 2026)
The development of digital technology has transformed the way we communicate, making interactions no longer dependent on face-to-face meetings. This change has given rise to the concept of cyber empathy, which is the ability to understand, feel, and show empathy in interactions conducted in the digital world. The purpose of this article is to examine the concept of empathy in psychology and map how empathy manifests in virtual communication. By applying a literature review method covering journals, books, and scientific publications from 2018 to 2024, this study identifies four main dimensions of cyber empathy: cognitive empathy, affective empathy, empathic responsiveness, and adjustment to digital media culture. The results show that empathy can develop optimally in online communication if individuals are able to interpret emotional contexts through writing, symbols, or interaction patterns, and possess good digital literacy and emotional intelligence skills. However, several challenges can hinder the quality of empathy, such as a lack of nonverbal signals, anonymity, conflicts arising from text, and digital fatigue. These findings confirm that cyber empathy is a crucial aspect for creating more humane, ethical, and supportive digital interactions. Increasing digital empathy is crucial for maintaining healthy interpersonal relationships and reducing the likelihood of miscommunication in the era of virtual communication.